2020
DOI: 10.3390/en13123275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Circuit Arrangement on the Thermal Performance of Double U-Tube Ground Heat Exchangers

Abstract: Given that the issue of variations in geometrical parameters of the borehole heat exchanger (BHE) revolves around the phenomenon of thermal resistance, a thorough understanding of these parameters is beneficial in enhancing thermal performance of BHEs. The present study seeks to identify relative changes in the thermal performance of double U-tube BHEs triggered by alterations in circuit arrangements, as well as the shank spacing and the borehole length. The thermal performance of double U-tube BHEs with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This fact introduces a penalization on the energy performance of the GCHP and, in some cases, even to a system failure [13]. Moreover, in a BHE field a crucial role is played by the circuit arrangement [14]. Performance differences between ASHPs and GCHPs have been recently shown by Safa et al [15] in a comprehensive study, comparing experimental and numerical results, and by Self et al [16].…”
Section: Introductionmentioning
confidence: 98%
“…This fact introduces a penalization on the energy performance of the GCHP and, in some cases, even to a system failure [13]. Moreover, in a BHE field a crucial role is played by the circuit arrangement [14]. Performance differences between ASHPs and GCHPs have been recently shown by Safa et al [15] in a comprehensive study, comparing experimental and numerical results, and by Self et al [16].…”
Section: Introductionmentioning
confidence: 98%
“…Concerning the heat generation system, in the literature, many papers have investigated the evaluation of the seasonal coefficient of performance (SCOP) of heat pumps, both geothermal [9][10][11][12] and air-source, also considering, in the latter case, the effect of the defrosting cycle [13]. Regarding the integration of heat pumps with solar panels, the so-called solar-assisted heat pump systems, the most used system considers a heat pump connected to photovoltaic panels [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Duicu's study [4] reported the advantages of using heat pumps as a renewable source of energy. Different studies are also related to the employment of ground sources heat pumps [5]; in those applications, the performance of the entire heating and cooling system is significantly affected by soil thermal properties [6] and the circuit arrangement of the ground heat exchanger [7]. Regarding ASHP, in the recent literature, the effects of climate conditions are investigated by Mouzeviris and Papakostas [8] with reference to Greece.…”
Section: Introductionmentioning
confidence: 99%